2022
DOI: 10.35848/1882-0786/ac516b
|View full text |Cite
|
Sign up to set email alerts
|

Body doping dependence of field-effect mobility in both n- and p-channel 4H-SiC metal-oxide-semiconductor field-effect transistors with nitrided gate oxides

Abstract: Both n- and p-channel SiC MOSFETs, the gate oxides of which were annealed in NO, with various body doping concentrations were fabricated. Despite the large difference in bulk mobility between electrons (1020 cm2/Vs) and holes (95 cm2/Vs), the maximum field-effect mobility in heavily-doped (~5×1017 cm−3) MOSFETs was 10.3 cm2/Vs for the n-channel and 7.5 cm2/Vs for the p-channel devices. The measurements using body bias revealed that the field-effect mobility in both n- and p-channel SiC MOSFETs is dominated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…After distinguishing the dominant scattering mechanisms in these devices, Hall measurements were carried out under the effect of body bias ( V BS ) so that the Hall mobility ( ) can be studied as a function of transverse electric field in the strong inversion regime. Recent studies [ 13 , 14 ] observed the effect of transverse electric field on mobility in the strong inversion regime maintaining a fixed carrier concentration. A constant carrier concentration realizes fixed screening from scattering centers and enables the assessment of the sole effect of surface roughness scattering on mobility.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After distinguishing the dominant scattering mechanisms in these devices, Hall measurements were carried out under the effect of body bias ( V BS ) so that the Hall mobility ( ) can be studied as a function of transverse electric field in the strong inversion regime. Recent studies [ 13 , 14 ] observed the effect of transverse electric field on mobility in the strong inversion regime maintaining a fixed carrier concentration. A constant carrier concentration realizes fixed screening from scattering centers and enables the assessment of the sole effect of surface roughness scattering on mobility.…”
Section: Resultsmentioning
confidence: 99%
“…A schematic diagram of these two charge distributions is shown in the left panel of Figure 1 . In Equation (2), is a constant with a value of 0.5 for n-channel and for p-channel Si MOSFETs at [ 19 , 20 , 21 , 22 ], which are considered the same for 4H-SiC [ 13 , 14 , 23 , 24 ], but this choice does not affect the results and may need further studies in a wider effective field range. is the dielectric constant, q is the electron charge, is the free carrier concentration, and N A is the p-well substrate doping concentration for n-channel MOSFETs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon cannot be interpreted simply on the basis of Coulomb scattering from acceptors in a p-type body. 23,24) Furthermore, the influence of scattering by trapped electrons is inevitable, 25) since numerous trapped electrons remain even after nitridation. Therefore, Coulomb scattering due to the trapped electrons and surface roughness scattering, which is dominant in the high-E eff region, are indistinguishable.…”
mentioning
confidence: 99%